Funny read-aloud plays with leveled parts : 12 reproducible, high-interest plays that help students at different reading levels build fluency - Martin, Justin McCory; Sirrell, Terry (New York : Scholastic, 2008)
Presents twelve reproducible read-aloud plays designed to help students in grades four through six at varying reading levels build their reading fluency skills.
5-8.
English.
Keywords: Oral reading; Readers' theater -- Study and teaching (Elementary); Reading (Elementary); Readers' theater -- Study and teaching; Reading